2014
DOI: 10.1038/bmt.2014.96
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in pediatric patients after allogeneic SCT: development of the PedsQL Stem Cell Transplant module and results of a pilot study

Abstract: With increased survival after pediatric allogeneic hematopoietic SCT health-related quality of life (HRQL) has emerged as an essential health outcome. The impact of transplant and chronic GVHD (cGVHD)-associated morbidity remains a major obstacle. In 2005, the National Institutes of Health (NIH) Consensus Conference on Criteria for Clinical Trials in cGVHD recommended HRQL tools as an independent measure of the impact of disease burden. The NIH recommendations did not provide a cGVHD-specific tool for HRQOL me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…Consistent with the finding of another study by Christakou et al [28] we observed that the lack of a pain scale within the ASKp is worth mentioning as many cGVHD patients especially with joint and fascia involvement and/or steroid side effects have pain along with their symptoms of cGVHD. We have previously published results from a prospective study on health-related quality of life after pediatric HSCT that most problems were detected within the domains of physical functioning and pain [12].…”
Section: K Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the finding of another study by Christakou et al [28] we observed that the lack of a pain scale within the ASKp is worth mentioning as many cGVHD patients especially with joint and fascia involvement and/or steroid side effects have pain along with their symptoms of cGVHD. We have previously published results from a prospective study on health-related quality of life after pediatric HSCT that most problems were detected within the domains of physical functioning and pain [12].…”
Section: K Original Articlementioning
confidence: 99%
“…Chronic GVHD is an extremely complex multisystemic chronic disorder with heterogeneous pathogenesis [6] and clinical manifestations resembling a variety of autoimmune diseases with involvement of many tissues and organs in adults, adolescent and pediatric patients [7,8]. Furthermore, cGVHD is associated with decreased survival, prolonged duration of immunosuppression [9], adverse physical functioning, disability [10] and decreased QOL [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the Working Group recommends exploration of the PedsQL based on results in other chronic illnesses and hematopoietic cell transplantation. 9395 …”
Section: Chronic Gvhd Non-specific Ancillary Measuresmentioning
confidence: 99%
“…514 Children undergoing HSCT require prolonged protective isolation given their vulnerability to infections and many of them are very sedentary while hospitalized and confined to their room. Prolonged immobility negatively affects multiple organ systems, including musculoskeletal, 1517 cardiovascular, 17,18 respiratory, 17,19 integumentary 17 and endocrine systems.…”
mentioning
confidence: 99%